Synthesis techniques, fundamental properties, and emerging applications of nanocomposites: A comprehensive review - Saha, Rijon; Munshi, Md. Hanif; Akter, Monira; Shikder, Abdullah Al Rakib; Islam, Tarikul (SPE polymers, 2025)
Nanotechnology has gained considerable attention for its potential to develop many fields by manipulating materials at an incredibly small scale. One of the important segments of nanotechnology is combining nanoparticles with traditional materials to enhance their properties. Composite materials have an inherent ability to modify the properties of the constituents to a greater extent. The nanocomposites further enable the process. Hence, this paper provides a thorough analysis of the technology and concepts of different types of nanocomposites, including their synthesis, properties, and applications. Due to their tiny size, nanoparticles have distinct properties like high reactivity, strength, and unique thermal, electrical, and antimicrobial characteristics. Their addition to any composite contributes to the development of stronger, more efficient, and versatile materials. The application areas of nanocomposites are expanding at a rapid pace. An in‐depth understanding of the effective synthesis of nanocomposites is essential for improving their performance and finding new ways to use them. Further innovations are being looked at in different areas, such as sustainable and cost‐effective manufacturing techniques of nanocomposites. The ongoing review article hence intends to provide an overall scenario on the types and synthesis methods existing currently and explores the areas where nanocomposites are being used as a better alternative to traditional materials. Highlights Understanding the synthesis and characterization methods to optimize nanocomposite properties and expand applications. Enhancing mechanical, thermal, and electrical properties in composites, while outperforming traditional materials. High reactivity, aspect ratio, and specialized properties boost nanocomposites' functionality. Improving efficiency and performance reduces material usage, extends lifespans, and promotes sustainability. Nanocomposites offer enhanced mechanical, thermal, electrical, barrier, and optical properties due to their unique nanostructure, making them suitable for diverse industrial applications.